Multivalent ruthenium immobilized by self-supported NiFe–organic frameworks for efficient electrocatalytic overall water splitting. Issue 6 (9th January 2023) - Jiang, Wei; Wang, Jia; Jiang, Yu; Wu, Yuanyuan; Liu, Bo; Chu, Xianyu; Liu, Chunbo; Che, Guangbo; Lu, Yang
Abstract : A Ru-doped and self-supported metal–organic framework/nickel–iron foam electrode demonstrates an efficient and durable electrocatalytic activity for overall water splitting. Abstract : Doping transition metal electrocatalysts with Ru is an effective strategy to achieve the balance between high-efficiency performance and low preparation cost. Herein, we prepared a series of Ru-doped and self-supported Ru x -NiFe-MOF/NFF electrodes under solvothermal conditions. In the synthesis process, some Ru 3+ ions were reduced to metallic Ru nanoparticles and further coated by NiFe-MOF sheets, while the residual Ru 3+ ions were diffused into the lattice of NiFe-MOFs. The optimal Ru9.1 -NiFe-MOF/NFF showed high electrocatalytic activity for the hydrogen evolution reaction (HER) with an overpotential of 17 mV @ 10 mA cm −2, which was much better than that of many reported catalysts. For the oxygen evolution reaction (OER), a low overpotential of 202 mV @ 10 mA cm −2 was required. When used as both an anodic and a cathodic electrocatalyst, the Ru9.1 -NiFe-MOF/NFF couple demonstrated outstanding overall water splitting performance with a cell voltage of 1.47 V @ 10 mA cm −2 . Moreover, the electrocatalytic activity of the bifunctional Ru9.1 -NiFe-MOF/NFF electrode could be maintained over 90 h. Based on analysis using various characterization techniques, the electrocatalytic performance of Ru9.1 -NiFe-MOF/NFF could be attributed to the intrinsic activity of Ru sites, the synergistic effect of various metal species, and the in situ transformation of Ni/Fe sites. This work provides insight into the design of a bifunctional Ru-doped electrocatalyst for overall water splitting.